The hare and the tortoise : aesop's fables - Hirata, Shogo (Tokyo : Joie, Inc, 1989)
One day a tortoise was walking along the road, when a hare came hopping toward him. "Hi, Mr. Tortoise! You're walking slowly as usual, I see. Why do your walk slowly?" The hare teased.
Keywords: Tortoise stories - Fiction